Dynamic Efficiency of a Container Crane's Hoisting Transmission System under Hoisting Dynamic Load. (13th March 2016) - Liu, Yuanyuan; Zhang, Qing; Qin, Xianrong; Sun, Yuantao
Abstract : The dynamic efficiency of hoisting transmission system on a container crane is fundamental for accurate efficiency prediction, while the dynamic efficiency of hoisting transmission system has not been investigated sufficiently. This paper will focus on dynamic efficiency of hoisting transmission system under hoisting dynamic load. A power loss model of gearbox was built. Then the dynamic model of gear transmission was developed including time-varying mesh stiffness and hoisting dynamic load was studied. Power loss, dynamic efficiency, and equivalent static efficiency were conducted in hoisting and lowering working conditions. The result shows that dynamic efficiency which consists of the significant lower frequency component coincided with hoisting load torque of the higher frequency component which is directly related to dynamic mesh and bearing force. And in two processes, the equivalent static efficiency in constant speed stage is min, whereas maximum value occurs in different stage. The research results lay a foundation for hoisting gear transmission dynamic efficiency analysis.